Sistem Informasi Pengelolaan Kegiatan Umat Hindu Di Kota Gorontalo - I Gusti Ngurah Buda Yadnya; Moh Hidayat Koniyo; Rahman Takdir (Gorontalo State University, 2021)
Abstract Hinduism is one of the religions in Gorontalo with an increasing believer over time due to a surge of wandering believers to Gorontalo City. As time goes by, there has never been a media used to process data of the believer so that it leads to ineffectiveness of search for location of those believers in Gorontalo City and also to express information about activity conducted by them. Therefore, the problems should be solved by an information system media to facilitate people in searching data of Hindu in Gorontalo City and to express the activity-related information. Method applied in this system development was prototype. Result of this research was a Hindu's activity management information system in Gorontalo City. The result is expected to be a data collection media of Hindu in Gorontalo City and to facilitate people in seeking the location of the believers in Gorontalo City as well as to be a media to express information related to activity organized by them. Keywords: Hindu, Gorontalo City, Prototype Method, Information System, Activity